Unaccompanied Girls with Precarious Odds. (3rd March 2021) - Hedlund, Daniel; Salmonsson, Lisa; Sohlberg, Tove
Abstract: Statistics made available by the Swedish Migration Agency (SMA) make it possible to follow first-decision outcomes in asylum cases concerning unaccompanied children (types of residence permits granted, percentage of rejections, etc.). Yet, we know little about differences in asylum decision outcomes for unaccompanied children coming to Sweden. Therefore, we wanted to find out how gender, country of origin, and asylum reports are associated with the likelihood of being granted residency. Asylum decisions concerning unaccompanied children were first coded inductively. These codes were later merged into larger categories that were analyzed quantitatively by logistic regression analysis. The data sample consisted of one calendar year of asylum decisions issued by the SMA. Results show that fewer girls than boys were granted asylum, and in fact, girls have an overall lower prospect of being granted residency. Results also display statistically significant gender differences in reported reasons for seeking asylum.